PENGARUH HALAL KNOWLEDGE, ELECTRONIC WORD OF MOUTH, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM PADA PRODUK KOSMETIK HALAL - Machbubah, Sa’idatun; Fahmi, Moh. Farih (Jurnal Ekonomika dan Bisnis Islam, 2024)
The research aims to determine and analyze the influence of halal knowledge, electronic word of mouth and product quality on muslim consumer’s purchasing decisions for halal cosmetic products in East Java. This research method uses quantitative methods with primary data gathered through questionnaries. The reseacrh sample consisted of 105 respondents selected randomly using a purposive sampling technique. The analysis was performed using Structural Equation Modelling (SEM) with the Partial Least Square (PLS) through SmartPLS 3.0. The results show that halal knowledge, electronic word of mouth, and product quality significantly influence muslim consumer’s purchasing decisions for halal cosmetic products in East Java. The implications of this research suggest that companies should focus on improving the dissemination of halal knowledge, encourage positive electronic word of mouth to strengthen consumer trust. Additionally, maintaining high product quality is essential in sustaining consumer loyalty and satisfaction.